Contraception concerns, utilization and counseling needs of women with a history of breast cancer: a qualitative study - Mody SK; Panelli DM; Hulugalle A; Su HI; Gorman JR (Dove Medical Press, 2017)
Sheila K Mody,1 Danielle M Panelli,1 Avanthi Hulugalle,1 H Irene Su,2 Jessica R Gorman3 1Division of Family Planning, Department of Reproductive Medicine, University of California, San Diego, San Diego, CA, USA; 2Division of Reproductive Endocrinology and Infertility, Department of Reproductive Medicine, University of California, San Diego, San Diego, CA, USA; 3College of Public Health and Human Sciences, Oregon State University, Corvallis, OR, USA Introduction: Reproductive-aged women who have had breast cancer face unique challenges when it comes to making decisions about contraception. Clinical guidelines indicate that patients should avoid pregnancy during cancer treatment, however the extent of contraception counseling and utilization after diagnosis has not been well studied.Methods: We conducted three focus groups and one semi-structured interview with women between the ages of 18 and 50 years old diagnosed with breast cancer within the last 5 years. We used clinic- and population-based recruitment methods to identify participants. Participants were asked a series of open-ended questions regarding their contraception decision-making and concerns at the time of their diagnosis, during treatment and afterward. We analyzed data to identify themes among participant responses.Results: A total of 10 women participated. We identified the following themes: 1) doctors treating cancer do not focus on reproductive health issues; 2) there is misinformation and lack of information on contraceptive options and risks; 3) women fear unintended pregnancy but have limited guidance on prevention; 4) peers are a trusted source of contraception information; and 5) information about contraception should be provided soon after diagnosis.Conclusion: Reproductive-aged breast cancer survivors have unique contraceptive concerns and may not be adequately informed about their contraceptive options. The results of this study may help guide and improve contraceptive counseling services for breast cancer survivors. Keywords: breast cancer survivors, contraception utilization, contraception counseling, peer counseling